The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/1099-0682(200112)2001:12<3067::aid-ejic3067>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigations of Sulfite-Bridged Binuclear Complexes of Platinum(II) and Palladium(II)

Abstract: Although analogous platinum(II) and palladium(II) compounds usually show similar chemical behaviour, different reaction products have been obtained on reaction of ethane-1,2-diamine bissulfitometallates(II) with the diaqua ethane-1,2-diamine metal(II) complexes of Pt and Pd. − The crystal structures of bis(µ-sulfito-1κS:2κO)bis[(ethane-1,2-diamine)-platinum(II)] trihydrate [(en)Pt(SO 2 O) 2 Pt(en)]·3 H 2 O (1) with parallel µ-(S:O) sulfite bridges, and of bis[(ethane-1,2-diamine)-µ-(S:O)-sulfitopalladium(II)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The conformation of 5 is staggered, much like what is observed for 1 – 3 . The Pt···Pt distance of 3.0583(4) Å is exceptionally short, with only three examples reported that exhibit shorter contacts between strictly Pt(II) centers as shown in Table . Despite having an exceptionally short Pt···Pt distance, 5 exhibits the longest S···S contacts between lanterns, with an average separation of 3.59(7) Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conformation of 5 is staggered, much like what is observed for 1 – 3 . The Pt···Pt distance of 3.0583(4) Å is exceptionally short, with only three examples reported that exhibit shorter contacts between strictly Pt(II) centers as shown in Table . Despite having an exceptionally short Pt···Pt distance, 5 exhibits the longest S···S contacts between lanterns, with an average separation of 3.59(7) Å.…”
Section: Resultsmentioning
confidence: 99%
“…Found: C, 22.98; H, 2.47; N, 4.03%. UV−vis−NIR(CH 2 Cl 2 ) (λ max , nm (ε M , cm −1 M −1 )): 266(37,300), 395(405)(sh), 487(128), 520 (39), 573 (19), 1233 (5). Evans method (CDCl 3 ): 5.06 μ B .…”
Section: ■ Introductionmentioning
confidence: 99%
“…The only method of their synthesis is the association of mononuclear fragments with sulfite anion in solution. For example, the following compounds were obtained this way: Ni[Co(en) 2 (SO 3 ) 2 ] 2 (H 2 O) 2 ·4H 2 O, [(en)Pt(SO 3 ) 2 Pt(en)]·3H 2 O, and [(en)Pd(SO 3 ) 2 Pd(en)]·3H 2 O . As one can see, there is a fundamental difference between this method and synthesis of the compound 3 .…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the literature data, we can assume that bridging SO 3 ligand appears in bands at 1070 and 864 cm –1 , and one more band at 1143–1157 cm –1 is overlapped with band from μ-SO 2 ligands. The band at about 1000 cm –1 corresponds to the vibrations of SO 2 groups. …”
Section: Resultsmentioning
confidence: 99%
“…Treatment of 1 with Oxone afforded the sulfite-bridged paramagnetic complex [(TpRu) 2 (μ-Cl)­(μ-pz)­(μ-SO 3 -κ 2 )] ( 5 ) in 86% yield (Scheme ) that was structurally characterized by X-ray crystallography (Figure ). Oxygenation of the sulfur atom resulted in elongation of the bridging S–O bond (1.830(6) Å), which is longer than that in [Pd­(NH 2 CH 2 CH 2 NH 2 )]­(μ-SO 3 -κ 2 ) (1.501(8) Å) . DFT calculations indicated that the electronic ground states of 1 and 5 are singlet and triplet, respectively (Figure S10).…”
mentioning
confidence: 98%